PENGARUH PENERAPAN MEDIA TUTORIALAUTOCAD TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI JURUSAN TKJ - Iistigna Iistigna; Hadi Gunawan Sakti (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
The Purpose research to be achieved in this study were to determine The Effect of AutoCAD tutorial Towards Students’ Creativity class XI at SMKN 9 Mataram in the academic year2018/2019. The method used in determining the subject of this research is used random samplingtechniques because the number of students is 136, so in this study the number of samples takenwas 34 students. The method used in obtaining the data of this study was the questionnaire mainmethod, documentation and observation as supporti ng method, while the data analysis methodused statistical analysis with the Chi-square formula. The results of the analysis obtained in thisstudy are the calculated X2 of 28.624 and X2 table of 9,488. Thus, was 28,624 > 9,488. This ismeans that the alternative hypothesis which that there was The Effect of Auto CAD tutorialTowards Students’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019 wasaccepted and the null Hypothesis that there is no The Effect of Auto CAD tutorial TowardsStudents’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019 was rejected.The conclusion obtained in this study was that there was The Effect of Auto CAD tutorial TowardsStudents’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019, which meansthe results of this study are significant with a t count of 28,624.